Would price-level targeting destabilise the economy? - Patrick Minford; Eric Nowell; Bruce Webb (Cardiff University, Cardiff Business School, 2005)
When indexation is endogenous price level targeting slightly adds to economic stability, contrary to widespread fears to the contrary. The aggregate supply curve flattens and the aggregate demand curve steepens, increasing stability in the face of supply shocks.
Keywords: E31; E42; E52; 330; Inflation; targeting; price-level rule; Price level target; indexation; monetary regime; endogenous contracts; stationarity; stability